Fish Marketing System in Nepalgunj Sub-Metropolitan City, Banke Lumbini Province, Nepal - Singh, Ankit Kumar; Chaudhary, Bhesh Raj; Prasad, Amarnath (Academia Research Journal, 2023)
The fish market is an active and complex industry that involves the purchasing and marketing of fish and related products. It is a crucial part of the comprehensive food system, providing a valuable source of protein and other essential nutrients to humans. The present study was carried out in the Nepalgunj sub-metropolitan city in Banke district, well known for fish varieties and traditional recipes. A total of 72 respondents including shopkeepers and workers from 25 shops were interviewed based on a semi-structured questionnaire, which included marketing structure, literacy of fish traders, knowledge of fish preservation and sanitation, resource preference, transportation system, demand & trade, and constraints of fish marketing. The study reported 14 fish species and one Penaeus species belonging to arthropods, also considered locally as a fish variety and imported to the Nepalgunj fish market as ‘Jhinggemachha’. The fish marketing system in Nepalgunj was reported poor and unsystematic in the lack of proper market infrastructure and facilities. The local government should develop a proper plan to monitor and improve the market hygiene and quality of products in the current fish marketing system.